Estudo dos polifenóis, atividade antioxidante e antimicrobiana da madeira e casca de Maclura tinctoria (L) D. Don ex Steud - Lamounier, Keli Cristina (2010)
In this original work, the specie Maclura tinctoria (L.) D. Don Ex Steud, as known as amoreira , was evaluated under many aspects. The macromolecular constituent s composition, the phenolic compounds level, antioxidant and antimicrobial activity of the bark and wood were studied. The corresponding percents of total extractives level, acid insoluble lignin (Klason´s lignin), acid soluble lignin, holocelluloses, hemicelluloses and α-celluloses were an average of the values for the wood: 10.79 ± 1.98; 21.47 ± 1.25; 1.28 ± 0,00; 69.43 ± 2.16; 23.59 ± 0.36; 46.02 ± 1.53 (%), and for the bark 50.64 ± 2.47; 18.77 ± 1.20; 0.45 ± 0.01; 29.14 ± 1.90; 8.78 ± 0.42 and 21.4 ± 0,77 (%). The level of total phenols obtained with methanol/water 4:1 (v/v) and acetone/water 7:3 (v/v) extracts using Folin-Ciocalteau method for the wood was 38.43 ± 0.42 and 45.34 ± 0.86 and 35.03 ± 0.94 e 43.17 ± 1.18 for the bark, expressed in Gallic acid equivalents (GAC) per gram of sample. The proanthocyanidins level obtained was 5.11± 0.59 for wood and 6.51 ± 0.62 for bark, in catechin equivalents per gram of sample. The antioxidant activity was determined by DPPH (2,2-diphenyl-1-picrylhydrazyl) for the wood and bark extracts, with IC50=18.74 and IC50 = 20.97 μg mL-1 , for wood and bark, respectively. The crude extracts from wood and bark from Maclura tinctoria (L.) has presented growth inhibition of the tested periodontopathogenic bacteria. The MIC of the crude extracts were in the range of 200 and 400 μg mL-1 for wood extracts and from 20 to 400 μg mL-1 for bark extracts, against the control microorganisms tested.